2018
DOI: 10.20471/acc.2018.57.04.03
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Complete Blood Count Parameters in Patients with Colorectal Cancer

Abstract: SUMMARY – Chronic inflammation has been linked with many cancers. It seems that easily available and usual blood inflammatory markers might serve as a prognostic factor for overall survival and disease-free survival in patients with various cancers. Preoperative neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), as well as hemoglobinemia, thrombocytosis, elevated C-reactive protein values, neutropenia and leukocytosis have been shown to affect overall survival and disease-free surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 11 publications
0
19
1
1
Order By: Relevance
“…The increase of the NLR level indicates a decrease in the lymphocyte level or an increase in the neutrophil count relative to that in normal patients. NLR has been proven to be closely associated with the prognosis of tumor patients, with higher PLR suggesting poor prognosis in lung cancer, 11 ovarian cancer, 23 colorectal cancer, 9 , 24 osteosarcoma 25 and gastric cancer. 10 Some studies have been conducted on the clinical significance of PLR and NLR in the prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of the NLR level indicates a decrease in the lymphocyte level or an increase in the neutrophil count relative to that in normal patients. NLR has been proven to be closely associated with the prognosis of tumor patients, with higher PLR suggesting poor prognosis in lung cancer, 11 ovarian cancer, 23 colorectal cancer, 9 , 24 osteosarcoma 25 and gastric cancer. 10 Some studies have been conducted on the clinical significance of PLR and NLR in the prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, another study with the cut-off of 1.0 × 10 9 /L for pre-operative lymphocyte count, Shibutani et al (32) showed that RFS and OS rates were significantly higher in the high-lymphocyte group compared with the low-lymphocyte group. On the contrary, no prognostic significance of pre-operative lymphocyte count was observed for both RFS and OS in another cohort of patients with colorectal cancer (33). The discrepancy findings between previous studies might be owing to the different cut-off values, and actually no reference of cut-off values has been recommended or established (36).…”
Section: Discussionmentioning
confidence: 88%
“…Colorectal carcinoma is the third most common cancer and has fatal outcome 9 . Preoperative CEA levels have shown relationship with disease prognosis in CRC.…”
Section: Discussionmentioning
confidence: 99%